DIFFICULTIES ENCOUNTERED BY THE FORENSIC UNIT PERSONNEL IN THE ANALYSIS OF EVIDENCES ON CRIME - Ibañez, Mary Jane G. (President University, 2024)
The primary goal of the study was to ascertain the challenges faced by the forensic unit staff when analyzing the evidence from crimes being investigated in Roxas City, including issues on laboratory operations, technological difficulties, health and safety issues, and cooperation and information sharing. The study used the descriptive research design. The data gathered were through the use of a researcher-make questionnaire which was statistically treated and analyzed with the aid of the Statistical Package for Social Sciences (IBM SISS Version 25). The research tools used were frequency count, percentage, mean and t-test/f-test as statistical tools to analyze and interpret the gathered data. Findings of the study revealed that the difficulties encountered by the forensic unit personnel in the analysis of evidence on crime was moderately high in the laboratory operations, technological challenges, but very high difficulty in safety concerns and collaboration and information sharing. There was no significant difference on the difficulties encountered by the forensic unit personnel in the analyzes of evidences on crime as to sex, years in service, educational attainment, estimated monthly income, but with significant difference in terms of age.